Hubungan antara Penggunaan Obat Nyamuk dengan Tingkat Kontrol Asma - Astuti, Astari Rindu; Aphridasari, Jatu; Widardo, . (Nexus Kedokteran Klinik, 2013)
Background: Asthma is a chronic inflammatory disorder of the airways with episodic symptoms such as cough, shortness of breath, wheezing, and uplifted chest. Mosquito repellent consists of chemical synthetic chemical materials that can prevent mosquitoâs bite towards. This study is to find out if there is or not any correlation between mosquito repellent usage and rate of asthma control. Methods: This study was an analytic observational study using cross sectional approach conducted on May to July 2013. Sixty samples were taken by using purposive sampling from outpatients who visited Pulmonary Clinics of Local Public Hospital Dr. Moewardi and fulfilled the inclusive criteria. The data was collected via interview by using a set of questionnaire. The data was then analyzed using Chi-Square test on Statistical Product and Service Solution (SPSS) 20.00 for Windows. Results: There is no significant correlation between mosquito repellent usage and rate of asthma control. From the Chi-Square test result, it was obtained that the significance value is p = 0,817. Conclusions: Based on this research, it can be concluded that there is no correlation between mosquito repellent usage and rate of asthma control. Keywords: mosquito repellent, rate of asthma control Â